From the margin to the mainstream reintegration into community life of prostituted women through informal education - Dedace, Ma. Justiniana Jumawa (2008)
This qualitative study describes the reintegration of prostituted women into community life as a transformative educational process. It focused on the identification of the reintegration initiatives provided by three NGOs and the knowledge, values and skills learned by the women. It also aimed to describe the methods of transmission used and to determine the empowering strategies that enabled the women to leave the flesh trade and reintegrate to community life. The study employed the grounded theory approach and used feminist research methodologies in conducting interviews and documenting training sessions. It was revealed that the combination of formal, nonformal and informal education in providing reintegration assistance inspired and motivated them to leave prostitution and reintegrate to their family or community.